Teaching Method of Choir for Non-Music Major Student in University in China - Zhile, Zhu; Nopparalai, Jakarayuth (Journal of Roi Kaensarn Academi, 2024)
Non-music majors in colleges and universities have weak basic knowledge of music. Because of the lack of basic music education in primary and secondary schools due to the pressure of senior high school entrance examination and college entrance examination, many students can’t squeeze time from academic pressure to learn music theory, solfeggio and ear training, let alone participate in chorus rehearsal. Take the choir of Lanzhou University of Technology as an example. Most students don’t know the staff, vocal music, music theory knowledge and solfeggio are in a zero-based state, and they have a vague concept of the choir. They just join the choir because they like singing and want to improve their vocal singing level. Therefore, it is difficult to ensure the sustainable development of chorus rehearsal. Although some students have poor foundation, they preview and review their works in advance because of their love, and many members are still in the stage of singing music because of academic and other objective reasons, resulting in the slow progress of chorus rehearsal. In view of the weak basic knowledge and uneven level of chorus members, colleges and universities should find out the reasons and start from various aspects to fundamentally solve the above problems in order to improve the rehearsal efficiency of chorus.